Software process models: a review and analysis - A. Haraty, Ramzi; Hu, Gongzhu (International Journal of Engineering and Technology, 2018)
Modeling of software process has been a very challenging problem and constantly debated in the software development community in the past 30+ years, largely due to the complex nature of the software development process that involves not only the technical knowledge and skills but also many other factors, such as human, management, quality assessment, and cost. Although the situations of creating software differ greatly from one case to another, there are some common themes shared by many of the situations, and hence various software process models have been emerged to address these common themes. In this paper, we present a review of the software process models commonly used in practice, from traditional to agile, and assessment of these models with metrics and case studies.